Productivity Study of Pigeon, Turquois, and Marlboro Discus Broodstock’s Strain (Symphysodon Discus) at Mischosella Fish Cipayung Farm - Kristiany, Maria Goreti Eny; Prabowo, Guntur (Politeknik Kelautan dan Perikanan Karawang, 2022)
Discus is one of the ornamental fish that lives in freshwater. Discus is a fish that is quite famous among ornamental fish lovers. Discus (Symphysodon discus) belongs to the Cichlidae family which comes from the calm waters of the Amazon river. This fish is also known as the King of Aquarium. Its body shape is round like a disc and its movements are smooth. Discus enthusiasts are numerous, and they are also creative to bring up new varieties that are better and more attractive, which are in demand by the public. All strains of discus fish are in demand by both local and export communities. At Mischosella Fish Cipayung Farm, 3 types of discus are cultivated, namely Pigeon, Turquois, and Malboro. These three types of discus have distinctive patterns and colors. The productivity of these three types of discus greatly influences the company's productivity in producing discus seeds. The purpose of this study was to determine the productivity of the Pigeon, Turquois, and Malboro discus at the Mischosella Fish Cipayung Farm and at the same time provide suggestions for the types of discus broodstock that need to be developed. The parameters observed in this study were brood spawning frequency, fecundity, hatching rate, and survival rate of discus larvae. Based on the results of the study, the spawning frequency was carried out by the Turquise species (9 times during the observation) while producing the most eggs (217 eggs). However, the highest hatching rate was produced by the Marlboro discus parent (96.26%). However, the highest survival rate was found in discus larvae produced by Turquise breeders (84.4%), and the highest ABL values were found in Marlboro and Pigeon. Water quality during larval rearing in the media for raising discus larvae for Pigeon, Turquise, and Marlboro types is in the same range, namely temperature 26 – 30.5oC, pH 6 – 6.8 and DO 5.5 – 6.3 mg/l. the optimum range for breeding discus seeds.